Response of Growth and Yield of Basil (Ocimum Sanctum L.) to Several Concentrations of Liquid Organic Fertilizers and Growth Regulators - Rio Hasten; Palupi Puspitorini; Tri Kurniastuti (Procedia of Engineering and Life Science, 2021)
This research was conducted to determine the interaction of combination treatment of liquid organic ferilizer and growth regulators with different concentrations on tthe growth and yield of basil plants (Ocimum sanctum L.). The research was carried out in March-May 2021 in Doko village, Blitar. The treatments were arranged in a factorial randomized block design (RAK Faktorial). The treatments in this study included 2 factors which were repeated 3 times. The first factor is the application of liquid organic fertilizer which consists of 3 levels, namely 0 (control), 5, and 10 ml/liter. The second factor is the application of growth regulators which consists of 3 levels, namely 3, 6, and 9 ml/liter. The variables observed included plant height, number of eaves, number of branches, and fresh weight. The results of the analysis of variance showed that there was a significant effect on the combination of dosages of liquid organic fertilizer and growth regulators on all observation variables, namely plant height, number of leaves, number of branches, and fresh weight. The best treatment combination is shown by the application of liquid organic fertilizer 10 ml/liter and growth regulators 9 ml/liter.